Effects of deep cryogenic treatment on friction and wear of EN24 steel against alumina under dry and lubrication conditions - Khun, Nay Win (2024)
As-received (AsRec) EN24 steel was treated with conventional heat treatment (ConHeatTreat) without tempering followed by deep cryogenic treatment (DeepCryoTreat) as a supplemental treatment to study its tribological behaviour against alumina without or with mineral oil (MO) under different normal loads of 1 N and 5 N. The ConHeatTreat of the AsRec-EN24 obtained an 218.5% improvement in its hardness as the supplemental DeepCryoTreat of the ConHeatTreat-EN24 resulted in a 11.7% further improvement in its hardness. As a result, the ConHeatTreat-EN24 had the 67.5% and 56.3% lower wear volumes for 1 N and 5 N under dry condition and the 53.6% lower wear volume for 5 N under MO lubrication condition compared to those of the AsRec-EN24, respectively. The DeepCryoTreat-EN24 had the 11.5% and 39.7% lower wear volumes for 1 N and 5 N under dry condition and the unmeasurable wear volume for 5 N under MO lubrication condition compared to those of the ConHeatTreat-EN24, respectively. It could be concluded that the supplemental DeepCryoTreat further improved the hardness and thereby the abrasive wear resistance of the ConHeatTreat-EN24 under both dry and lubrication conditions.